Spremljanje intervencij kliničnih farmacevtov v Splošni bolnišnici Murska Sobota - Kovačič, Alenka (Anali PAZU, 2023)
Clinical pharmacists have been part of the health care team for many years. The number of employed clinical pharmacists varies widely among hospitals. Still the question remains, how to evaluate work of clinical pharmacists. In Murska Sobota General Hospital, we evaluated the work of clinical pharmacists by different departments from 1/1/2020 to 31/12/2020. The services of three clinical pharmacists in SBMS were included in the analysis. In one year, 8,523 different interventions were introduced. 30 different interventions were monitored, as well as attendance at reports and/or rounds with other medical staff. Among the interventions, the most frequently was: therapy review of the hospitalized patient's (1,979 times), review of interactions between examined drugs (1,859 times) and review of the history of treatment with drugs and food supplements upon admission (1,785 times). Evaluation of the work of clinical pharmacists in hospitals is an important step towards work monitoring, also an upgrade of this system with subsequent measurement of the quality of the services provided would be welcome.
Keywords: drug treatment history; farmakoterapijski pregledi; kakovost; merjenje dela; pharmacotherapy review; pregled terapije; quality; therapy review; work measurement; zgodovina zdravljenja z zdravili